Rare earth metals as a component of the national safety in mineral resources - Kal'co, A.D.; Bobliakh, S.R. (Київський національний університет імені Тараса Шевченка, 2012)
In this article the analysis of use and extraction technologies of rear earth metals are presented. Examples of the impact of those metals on the world economy and politics are showed. In addition, the environmental impacts of the mining industry and questionі of the national safety of Ukraine in those raw materials were observed.

В статті проаналізовані використання та технології вилучення рідкісних земельних металів. Наведені приклади впливу цих металів на світову економіку та політику. Також розглянуті деякі аспекти впливу гірничодобувної промисловості на довкілля та питання забезпеченості України цією сировиною.

В статье проанализированы использование и технологии извлечения редкостных земельных металлов. Представлены примеры влияния этих металлов на мировую экономику и политику. Также рассмотрены некоторые экологические аспекты влияния горной промышленности на окружающею среду и вопросы обеспечения Украины этим сырьем.
Keywords: rare earth metals; environmental aspects; recycled materials; solution mining; pollution